Analisis Metodologi Pengajaran yang diaplikasikan Kitab Amtsilati Karya Taufiqul Hakim dalam Mempelajari Tata Bahasa Arab - Moh. Ali Ghafir (STAI Syaichona Moh. Cholil Bangkalan, 2019)
Amtsilati is one of the Arabic grammar books which has special characteristics compared to other books. This book is intended so that students can master in reading and giving meaning to the yellow book even though it is only a beginner level. This book does not target students to be able to communicate using Arabic, because the method is only emphasizing reading and giving meaning to the yellow book. There are several learning methods that were applied when the Amtsilati instructor, including: lecture methode, question and answer, discussion, memorization, takrar (repeating material) and qiraah jama'iyah (reading collectively). The system of compiling the discussion material in the book Amtsilati begins with a discussion of the jar, isim dhamir, isim isyarah and so on. While the method of presenting the material follows the method of Tariqah al-istiqraiyah or the research method (inductive), that is by providing examples of material to be discussed, then analyzing the rules. Very different from the Arabic grammar books in general.